Governmental and Nonprofit Accounting: A Book of Readings (Book). - Hendrickson, Harvey S.; Knechel, W. Robert (The Accounting Review, 1985)
Abstract Reviews the book "Governmental and Nonprofit Accounting: A Book of Readings," by Leonard Eugene Berry and Gordon B. Harwood.